1992
DOI: 10.2307/30146493
|View full text |Cite|
|
Sign up to set email alerts
|

Two Outbreaks of Primarily Noninvasive Group A Streptococcal Disease in the Same Nursing Home, New York, 1991

Abstract: Group A Streptococcus has been identified as the cause of several outbreaks of infection in residents of nursing homes. These reports described outbreaks that included persons with severe invasive disease as well as more limited infection. The purpose of this report is to describe an investigation of two consecutive outbreaks of group A Streptococcus that occurred in a single nursing home, where all affected residents had disease of mild to moderate disease severity. This report focuses on the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Having frequent visitors was found to be a risk factor for carriage of the outbreak strain in a Georgia outbreak; however, review of concurrent invasive GAS cases in a larger Georgia population did not identify community infections caused by the outbreak strain [25]. Four other investigations that assessed the role of having frequent visitors did not find an association with elevated risk of disease or carriage [23,26,27,32].…”
Section: Cluster and Outbreak Investigationsmentioning
confidence: 73%
See 4 more Smart Citations
“…Having frequent visitors was found to be a risk factor for carriage of the outbreak strain in a Georgia outbreak; however, review of concurrent invasive GAS cases in a larger Georgia population did not identify community infections caused by the outbreak strain [25]. Four other investigations that assessed the role of having frequent visitors did not find an association with elevated risk of disease or carriage [23,26,27,32].…”
Section: Cluster and Outbreak Investigationsmentioning
confidence: 73%
“…The role of staff in initiating or propagating GAS infection outbreaks is supported in several other investigations, including 2 investigations in which immobilized, isolated patients appeared to serve as reservoirs of infection from which staff repeatedly recirculated the organism among other residents [24,29]. In multiple instances, investigators found that staff members with GAS pharyngitis had cared for case patients prior to the outbreaks [23,30,33], although isolates were not available to confirm that staff and patient cases were due to the same strains.…”
Section: Cluster and Outbreak Investigationsmentioning
confidence: 94%
See 3 more Smart Citations